HOW @RICOWAAS INSTAGRAM ELECTION CONTENT SHAPES STUDENT POLITICAL AWARENESS AT UIN SUMATER UTARA - Nayla Kamila; Anang Anas Azhar (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
We analyzed how Pilkada content on the @ricowaas Instagram account shapes political awareness among students at UINSU. To do this, we studied posts from the 2024 Medan City Pilkada campaign and interviewed eight students. We found that the content mostly highlighted personal branding, community interactions, and campaign promises. It helped increase student knowledge, though it did not directly dictate their voting choices. Students showed different levels of awareness. Some focused on simple visual branding, while others practiced critical awareness, verifying facts, comparing sources, and weighing actual work programs before forming an opinion. Ultimately, our research shows that social media’s true value is not just in grabbing attention; it is in sparking critical thinking. Thus, political actors should use social media for voter education, not only to spread one-way messages but also to create spaces for dialogue that build political literacy among young people.